Intelligent heat flow control of double skin facade systems : doctoral thesis - Eškinja, Zdravko (Z. Eškinja ; Fakultet elektrotehnike i računarstva, 2019)
Double skin façades are frequently used in modern civil engineering, especially in high buildings with the glass envelope. With the development of technology, new possibilities have occurred to upgrade Double Skin Façades into an intelligent system. This dissertation presents such a novel design for a double skin façade system and appropriate control method. Therefore, the system analysis has been performed from the perspective of desired temperature homogeneity, with a goal to achieve equal comfort in the interior. Furthermore, the applied neural network control method is proved to be the best choice for the heat flow control as an immeasurable state variable. Estimation methods have been analysed as a part of a novel control algorithm. Computer simulations on a mathematical model and experimental tests on the scaled model have shown that it is possible to achieve better thermal conditions in interiors with Double Skin Façades. Since, the used control algorithm has significant adaptive property, the method is not constrained with dimensions, but the only structure, what justifies performing tests on a scaled model.As a result of this research, the original scientific contributions have been achieved and can be summarized as follows: 1. A novel method for automatic control of corridor double skin façade systems is proposed and tested. This method can equalize the interior temperature, with the purpose of increasing user comfort and is simple enough to be used by non-experts. 2. Artificial Adaptive Neural Network (AANN) is proven to perform better than conventional PI regulator for heat control in DSF corridor. Comparative analysis of non-controlled corridor double skin façade systems and automatically controlled double skin façade systems is per-formed. Controlled versus non-controlled heat ﬂow in DSF shows advantages of the controlled solution. Keywords: double skin façade, adaptive neural control, simulations, experiments, scaled modelling